2022
DOI: 10.1098/rstb.2021.0266
|View full text |Cite
|
Sign up to set email alerts
|

Immune function of the serosa in hemimetabolous insect eggs

Abstract: Insects comprise more than a million species and many authors have attempted to explain this success by evolutionary innovations. A much overlooked evolutionary novelty of insects is the serosa, an extraembryonic epithelium around the yolk and embryo. We have shown previously that this epithelium provides innate immune protection to eggs of the beetle Tribolium castaneum. It remained elusive, however, whether this immune competence evolved in the Tribolium lineag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…In other gene families, large changes in copy number have been found to be adaptive and related to certain environments or behaviors ( Briscoe et al 2013 ; Cheng et al 2017 ; Rane et al 2019 ; Chakraborty et al 2021 ). The Shx genes are expressed in the serosa during development, an extraembryonic tissue implicated in innate immunity and desiccation resistance in insects ( Panfilio 2008 ; Jacobs et al 2013 , 2014 , 2022 ). It is therefore possible that Shx duplication is an adaptation associated with modifications to the egg, and indeed, many of the highly duplicated genes show increased rates of sequence evolution ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In other gene families, large changes in copy number have been found to be adaptive and related to certain environments or behaviors ( Briscoe et al 2013 ; Cheng et al 2017 ; Rane et al 2019 ; Chakraborty et al 2021 ). The Shx genes are expressed in the serosa during development, an extraembryonic tissue implicated in innate immunity and desiccation resistance in insects ( Panfilio 2008 ; Jacobs et al 2013 , 2014 , 2022 ). It is therefore possible that Shx duplication is an adaptation associated with modifications to the egg, and indeed, many of the highly duplicated genes show increased rates of sequence evolution ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[48,51]). Downstream, RNA-seq after RNAi and pathogen-challenge studies have identified factors for serosal tissue maturation and physiology [24,55,56].…”
Section: Deciphering the Genetic Signature Of The Amnionmentioning
confidence: 99%
“…Many purported tissue-scale functions of polyploidy are probably applicable in this outer EE tissue. Serosal tissue integrity as a barrier epithelium of large cells confers cellular protection via detoxification [130] and innate immune responses to infection [55,56]. Furthermore, in many insect species, the serosa secretes a substantial cuticle that provides desiccation resistance [131][132][133] and mechanical protection [24].…”
Section: Polyploid Genomic Architectures Underpin Extraembryonic Tiss...mentioning
confidence: 99%
“…Although insect eggs are protected by the egg shell and the underlying vitelline membrane, they can be infected by pathogens through transovarial transmission or penetration of the eggshell [13,14]. Recent advances indicate that insect eggs can harbor endogenous immune defenses through the production of proteins by the serosa, an extra-embryonic tissue [15,16]. However, the serosa was secondarily lost in a group of derived flies (the Schizophora), which includes the wellstudied model insect D. melanogaster [17,18].…”
Section: Introductionmentioning
confidence: 99%